Assessing Language Vitality: Overview of Exisiting Models - Maklakova Evgeniya Mikhaylovna, Slavina Liliya Rustamovna, Mustafina Jamila Nasyhovna,; Maksimova Elvira Vladimirovna, Gataullina Kamila Nailevna, Ganieva Gulnara Ramilevna, (Opción, 2019)
The article deals with the question of multidimensionality and complexity of creating a model assessing the linguistic vitality. A comparative analysis of the existing models corresponding to the sociolinguistic paradigm is presented. The problems and difficulties associated with machine data processing are considered. As a result, risks of future language losses are especially high in the tropics and in the Himalayas, as these regions harbor many small-population languages and are undergoing rapid economic growth. In conclusion, Machine data processing and machine learning are the most important stages of processing the actual base of language behavior.